The Existence of Indonesian National Research and Innovation Agency: The Academic Freedom’s Perspective - Muhamad Dzadit Taqwa; M. Irfan Dwi Putra; Muhamad Ali Muharam (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
Recently, Indonesia has taken a policy to merge all the research institutions, which were classified as non-ministerial institutions, into the National Research and Innovation Agency (BRIN –Badan Riset dan Inovasi Nasional). The BRIN is expected to (1) reduce the research costs for the research institutions; and (2) integrate and harmonize these institutions. On the other hand, the policy has drawn constitutional law scholars' attention. Many of them who concern that BRIN intervenes academic freedom in Indonesia. The main factor that causes the concern is the subordinate relationship between the President and the BRIN that restrain researchers from their academic activities. This study aims to reveal the potential problem in the light of academic freedom. This study is of position to argue that the existence of the BRIN will not become an issue if it does not disrupt the essential aspects of academic freedom. However, the necessity and the urgency of its existence still draws questions.DOI: https://doi.org/10.22304/pjih.v9n1.a6